Spatio-temporal changes of glaciers, geomorphology, and meteorological influences on debris flow in the alpine environment: insights from a case study in the Hopar Nagar Valley, Northern Pakistan - Hussain, Abrar; Liu, Jingfeng; Ali, Muzaffar; Hassan, Wajid; Wang, Chengyuan (Geomatics, Natural Hazards and Risk, 2025)
Alpine environments are becoming increasingly vulnerable to climate change, as retreating glaciers and abrupt weather shifts lead to frequent flooding and debris flows globally. Particularly in the Karakoram region, glacier retreat driven by global warming reduces ice volume, leading to many catastrophic hazards associated with glaciers, such as debris flows and flooding. The infrastructure and communities in the Karakoram region are exposed to numerous glacier hazards. Climate change, glacial dynamics, and geomorphology regulate the nature and frequency of debris flow. To understand this concept, we selected four alpine catchments proven to frequent debris flow and flooding in the Hunza basin, Northern Pakistan. In this study we investigated the relationship between climate change, glacial dynamics, and geomorphological settings for debris flow in alpine environments. Our analysis revealed a significant snow glacier recession from 1993-2023. All glaciers have experienced slightly negative mass balance of -0.03 +/- 0.1 m w.e. a-1 from 2000-2020. Both in-situ and ERA5 climate data revealed extreme air temperature before debris flows followed by heavy rainfall, which triggered multiple debris flow events in August 2022. We selected these debris flow events in the Hopar Valley as a case study, which inflicted more than 30 million PKR on downstream infrastructure.